ADVERSE PHYSICAL EFFECTS OF ANTIRETROVIRAL THERAPY AND METHADONE ON PEOPLE LIVING WITH HIV/AIDS (PLWHA) USING INJECTION DRUGS (IDUS) - Idramsyah Idramsyah; Anditha Ratnadhiyani; Sahran Sahran (Bajang Institute, 2022)
Background: People with HIV who use injecting drugs besides taking ARVs also use methadone. With these conditions, of course there will be a risk of causing various side effects. Based on this, researchers are interested in exploring the physical side effects experienced by PLWHA IDUs while using ARV therapy and Methadone. Method: This qualitative research uses a phenomenological study approach. Participants were taken based on criteria referring to the purposive sampling technique (snowball sampling). Participants were PLWHA with a history of injecting drug users (IDU) aged 20 years and over and had undergone ARV therapy and Methadone maintenance therapy for at least 6 months. Researchers conducted semi-structured in-depth interviews and used Colaizzi's data analysis stages. Results: HIV AIDS sufferers who inject drug users experience physical side effects on the digestive system, namely tooth decay, constipation, anorexia. Side effects on the musculoskeletal system include muscle pain and weakness and insomnia. Side effects of the covering system are the appearance of itching and rashes. Side effect on the reproductive system is a decrease in sexual function. Recommendation: The results of this study need to be followed up with studies with a larger number of participants so that they can represent other problems experienced by PLWHA while using ARV therapy and methadone together.